2020
DOI: 10.1016/j.isci.2020.101669
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Acquired Rift Valley Fever Virus Neutralizing Antibodies Predominantly Target the Gn Glycoprotein

Abstract: Summary Rift Valley fever (RVF) is a viral hemorrhagic disease first discovered in Kenya in 1930. Numerous animal studies have demonstrated that protective immunity is acquired following RVF virus (RVFV) infection and that this correlates with acquisition of virus-neutralizing antibodies (nAbs) that target the viral envelope glycoproteins. However, naturally acquired immunity to RVF in humans is poorly described. Here, we characterized the immune response to the viral envelope glycoproteins, Gn and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 51 publications
3
31
0
Order By: Relevance
“…It has been postulated that placement of the Gn shields the hydrophobic fusion loop of the Gc, preventing premature fusion. Shielding of the Gc is consistent with sera binding data from RVFV infected individuals [ 181 ], which demonstrated that antibodies preferentially target the Gn. Further cryoET imaging and reconstructions of acidified RVFV have given clues to the repositioning of the Gn and are consistent with the requirement for Gc to extend towards the target membrane [ 151 ].…”
Section: Structure Of Bunyavirus Envelope Glycoproteinssupporting
confidence: 83%
“…It has been postulated that placement of the Gn shields the hydrophobic fusion loop of the Gc, preventing premature fusion. Shielding of the Gc is consistent with sera binding data from RVFV infected individuals [ 181 ], which demonstrated that antibodies preferentially target the Gn. Further cryoET imaging and reconstructions of acidified RVFV have given clues to the repositioning of the Gn and are consistent with the requirement for Gc to extend towards the target membrane [ 151 ].…”
Section: Structure Of Bunyavirus Envelope Glycoproteinssupporting
confidence: 83%
“…This model is very similar to the one proposed for the fusion of flaviviruses, which are unrelated enveloped viruses with a class II viral fusion glycoprotein [ 82 ]. Interestingly, antibodies exhibit much higher neutralizing activities in vitro and in vivo when they target G N rather than G C [ 88 , 89 , 90 ]. It has been proposed that anti-G N neutralizing antibodies block the fusogenic rearrangement of the G N -G C array by targeting the G N distal domain [ 91 , 92 ].…”
Section: Fusion and Penetration Of Phenuiviruses Into The Cytosolmentioning
confidence: 99%
“…Therefore, it will be important to determine if MAb therapy can prevent progression to late-onset encephalitis and the role of Fc effector functions therein, as this is where MAbs have the most human promise. Recent work in humans found that the antibody response to naturally acquired infection preferentially targets Gn, with neutralizing anti-Gn IgG responses lasting decades ( 42 ). Future investigation into the contribution of Fc effector functions in the human humoral response could further increase understanding of how antibody-mediated immunity protects against RVFV disease.…”
Section: Discussionmentioning
confidence: 99%